2016
DOI: 10.1080/02670836.2016.1160195
|View full text |Cite
|
Sign up to set email alerts
|

Wear resistance of Fe-based amorphous coatings prepared by AC-HVAF and HVOF

Abstract: amorphous coatings have been prepared by the activated combustion high velocity air fuel (AC-HVAF) and high velocity oxygen fuel (HVOF) processes. The microstructure and wear resistance of the amorphous coatings are comparatively studied. The wear volume loss of the AC-HVAF coating is approximately seven times less than that of the HVOF coating, indicating that the AC-HVAF coating exhibits better wear resistance. Detailed analysis on the worn surface indicates that the enhanced wear resistance of the AC-HVAF c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 30 publications
(56 reference statements)
0
18
0
Order By: Relevance
“…The average roughness of uncoated mild steel, SS202, and SS304 is observed as 2.45, 1.35, and 1.38 µm, whereas the values were 4.89, 4.63, and 4.58 µm after deposit coating. The investigators suggested that cutting, fracture, and abrasion are the major modes of erosion wear mechanisms that are relevant to slurry pipelines [2,3,13,14]. The eroded images of WC-10 Co 4 Cr-coated mild steel, SS202, and SS304 with EDS (energy dispersive spectroscopy) are shown in Figures 6-8.…”
Section: Visual Examination Of Eroded Coated Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The average roughness of uncoated mild steel, SS202, and SS304 is observed as 2.45, 1.35, and 1.38 µm, whereas the values were 4.89, 4.63, and 4.58 µm after deposit coating. The investigators suggested that cutting, fracture, and abrasion are the major modes of erosion wear mechanisms that are relevant to slurry pipelines [2,3,13,14]. The eroded images of WC-10 Co 4 Cr-coated mild steel, SS202, and SS304 with EDS (energy dispersive spectroscopy) are shown in Figures 6-8.…”
Section: Visual Examination Of Eroded Coated Surfacesmentioning
confidence: 99%
“…These coatings can provide a hard layer of carbides, oxides, and nitrides of Cr, W, Al, and Ti [10,11]. The high-velocity oxy-fuel (HVOF) technique can be applied to deposit coatings with high cohesive strength and superior mechanical properties [10][11][12][13][14]. In the present work, erosion wear behavior of three piping materials, namely, mild steel, SS202, and SS304, have been analyzed with and without a HVOF-sprayed WC- 10 Co 4 Cr coating.…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous alloys have attracted wide attention because of their excellent mechanical properties (Sharma et al , 2016; Inoue and Takeuchi, 2011). Compared to the crystalline alloys, amorphous alloys with no defects of dislocations and grain boundaries represent features of high hardness, excellent wear resistance and corrosion resistance (Liu et al , 2021; Ma et al , 2017; Pang et al , 2002). However, it is difficult to prepare large-size bulk amorphous alloys because of the limitation of preparation method in size and the performance of high brittleness (Liu and Zhang, 2014; Wang et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [9] and Matteo Federici et al [10] report that among the various thermal spraying techniques, the HVOF process is known for its high kinetic energy value and relatively low flame temperature. This favors the formation of an amorphous structure with decreased porosity and oxide content, resulting in better resistance to wear, corrosion and adhesion of coatings [11][12][13].…”
Section: Introductionmentioning
confidence: 99%